Periodontal Dressing-containing Green Tea Epigallocathechin gallate Increases Fibroblasts Number in Gingival Artifical Wound Model - Ardisa U. Pradita; Agung P. Dhartono; Catur A. Ramadhany; Ali Taqwim (Faculty of Dentistry, Universitas Indonesia, 2014)
<!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Green tea leaf (Camellia sinensis) is one of herbal plants that is used for traditional medicine. Epigallocatechin gallate (EGCG) in green tea is the most potential polyphenol component and has the strongest biological activity. It is known that EGCG has potential effect on wound healing. Objective: This study aimed to determine the effect of adding green tea EGCG into periodontal dressing on the number of fibroblasts after gingival artificial wound in animal model. Methods: Gingival artifical wound model was performed using 2mm punch biopsy on 24 rabbits (Oryctolagus cuniculus). The animals were divided into two groups. Periodontal dressing with EGCG and without EGCG was applied to the experimental and control group, respectively. Decapitation period was scheduled at day 3, 5, and 7 after treatment. Histological analysis to count the number of fibroblasts was performed. Results: Number of fibroblasts was significantly increased in time over the experimental group treated with EGCG periodontal dressing compared to control (p<0.05). Conclusion: EGCG periodontal dressing could increase the number of fibroblast, therefore having role in wound healing after periodontal surgery in animal model. DOI: 10.14693/jdi.v20i3.197 <!--[if gte mso 9]> <w:LsdException Locked="false" Priority="60" S